The overlap between Essential tremor and Parkinson disease. (January 2018) - Algarni, Musleh; Fasano, Alfonso
Abstract: Introduction: Essential tremor (ET) and Parkinson's disease (PD) are common disorders especially in the aging population and can have overlapping features that can make it difficult to differentiate between the two. In addition, a possible overlap from a pathophysiological standpoint has been often advocated in the past. Methods: In this review article, we gather the recent evidence in favor or against a possible relationship between ET and PD. This exercise follows the new advances in the field of tremor from both a pathophysiological and nosological perspective. Results: Dividing ET patients into early onset and late onset disease subtypes can prove useful in ascertaining the phenotypic, epidemiological and genetic characteristics defining its relationships to PD. The only way to ascertain whether ET increases the risk of future PD would be to conduct a longitudinal cohort study on early-onset ET patients. On the other hand, ET-plus patients or late-onset cases with ET of short-duration might represent a group of PD patients in their pre-diagnostic phase after the pre-motor stage. Conclusion: In spite of the growing body of literature in recent years of an overlap between ET and PD, we are far from elucidating the relationship (if any) between these two common disorders.